2016
DOI: 10.1038/srep32179
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Reduction of Parenchymal Cerebral Blood Flow in Mice with Bilateral Common Carotid Artery Stenosis

Abstract: The bilateral common carotid artery stenosis (BCAS) mouse model, which replicates chronic cerebral hypoperfusion and white matter ischemic lesions, is considered to model some aspects of vascular cognitive impairment. Cerebral blood flow (CBF) changes in the brain surface post-BCAS have been demonstrated by laser speckle flowmetry, but CBF levels in the brain parenchyma remain unknown. Adult C57BL/6J male mice were subjected to BCAS using external microcoils. Brain magnetic resonance angiography (MRA) was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 19 publications
7
44
0
Order By: Relevance
“…This study also demonstrated that CBF assessed by arterial spin-labeled perfusion-magnetic resonance imaging (ASL-MRI) was correlated with FDG-PET measurements in patients with AD. Similarly, ASL-MRI methods in the BCAS mouse model showed subcortical CBF reduction over at least a 30-days period after BCAS (29). Our preliminary ASL data also showed that prolonged reduction of CBF in BCAS model was sustained over longer period of 16 weeks.…”
Section: Discussionsupporting
confidence: 72%
“…This study also demonstrated that CBF assessed by arterial spin-labeled perfusion-magnetic resonance imaging (ASL-MRI) was correlated with FDG-PET measurements in patients with AD. Similarly, ASL-MRI methods in the BCAS mouse model showed subcortical CBF reduction over at least a 30-days period after BCAS (29). Our preliminary ASL data also showed that prolonged reduction of CBF in BCAS model was sustained over longer period of 16 weeks.…”
Section: Discussionsupporting
confidence: 72%
“…However, a maximum reduction of CBF to approximately 50% of baseline occurred within 2 hours post-surgery, followed by a progressive recovery of CBF to approximately 80% of baseline by day 30 (Shibata et al, 2004). Also, a similar acute reduction of CBF to ~50% of baseline was observed on the first day in other studies (Kitamura, et al, 2016; Srinivasan et al, 2015; Hattori et al, 2016). Growth of collateral vessels occurs only after a few days of hypoperfusion resulting in a recovery of CBF over time (Srinivasan et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…) by reducing blood flow in both cortical and subcortical structures over a sustained period (Hattori et al . ). The BCAS model shares several pathological consequences with cerebral SVD including microinfarcts, microhaemorrhages and WM disruption (Holland et al .…”
Section: Contribution Of Laboratory Animal Studiesmentioning
confidence: 97%
“…The original BCAS experimental model ) established in mice is most relevant to produce cerebral hypoperfusion (Tomimoto et al 2003) by reducing blood flow in both cortical and subcortical structures over a sustained period (Hattori et al 2016a). The BCAS model shares several pathological consequences with cerebral SVD including microinfarcts, microhaemorrhages and WM Fig.…”
Section: Contribution Of Laboratory Animal Studiesmentioning
confidence: 99%